A Secure Authentication mechanism for wireless sensor network using standardized IoT protocols (International Journal of Engineering and Computer Science, 2024)
Next-generation wireless sensor networks comprise low-cost, power-constrained nodes with limited data transfer, memory, and computational abilities, forming the backbone of IoT deployments across diverse domains. IoT sensor nodes play a pivotal role in collecting and disseminating critical environmental data using protocols like MQTT. However, ensuring secure communication channels between nodes remains paramount, necessitating robust measures for authentication, confidentiality, and data integrity. This abstract introduces a secure mechanism tailored for next-gen wireless sensor networks, employing the MQTTS (MQTT over TLS) IoT protocol. The proposed mechanism aims to bolster network defenses against various attacks, including masquerade, man-in-the-middle, replay, password guessing, and denial-of-service attacks, ensuring the resilience and reliability of next-gen IoT deployments.